To the “serious reader”: the influence of John Wesley’s a christian library on methodism, 1752-1778 - Holgerson, Timothy W. (Kansas State University, 2011)
After years of selecting, editing, omitting, reducing and correcting what would become printed as over fourteen thousand pages of devotional literature for a young Methodist movement in the wake of the English Evangelical Revival, John Wesley pronounced his A Christian library: consisting of extracts from, and abridgments of, the choicest Pieces of practical divinity which have been published in the English tongue in fifty volumes (1749-1755) an underappreciated treasure and an overtaxing expenditure. Taking their lead from Wesley’s comments, scholars and historians of Wesley studies and Methodism have neglected to take a closer look at the ways the library may have been successful. This study argues that despite being initially a marketing disappointment and an expensive liability, John Wesley’s Christian library was influential in helping to shape the spiritual lives of “serious readers” within Methodism, particularly from 1752-1778. In the preface to the Christian library, Wesley revealed his standard for measuring the influence of the Library. However, despite offering a premature and partial assessment of the library in his journal entry at the end of 1752, providing some public responses to criticisms of the library in 1760 and again in the early 1770s, and writing some personal letters that recommended the library to others in the 1780s, Wesley did not publish an evaluation of what he believed the Christian library had accomplished during his life. Thus, based on the collaborative evidence gathered from the personal accounts of early Methodist preachers and the final address of Francis Asbury to American Methodists, this study makes the case that Wesley’s Christian library had a substantial positive influence on Methodism.
Keywords: John Wesley; Christian library; Methodism; Serious reader; History (0578); History, Church (0330); Religious History (0320)